B4GALT5 a sialylation-related genes associated with patient prognosis and immune microenvironment in ovarian cancer and pan-cancer - Di Wu; Li-yuan Sun; Xin-yu Chang; Guang-mei Zhang (BMC, 2024)
Abstract Background Ovarian cancer (OC) is the predominant primary tumor in the human reproductive system. Abnormal sialylation has a significant impact on tumor development, metastasis, immune evasion, angiogenesis, and treatment resistance. B4GALT5, a gene associated with sialylation, plays a crucial role in ovarian cancer, and may potentially affect clinicopathological characteristics and prognosis. Methods We conducted a comprehensive search across TIMER, GEPIA2, GeneMANIA, and Metascape to obtain transcription profiling data of ovarian cancer from The Cancer Genome Atlas (TCGA). The expression of B4GALT5 was test by immunohistochemistry. To investigate the impact of B4GALT5 on growth and programmed cell death in OC cells, we performed transwell assays and western blots. Results The presence of B4GALT5 was strongly associated with an unfavorable outcome in OC. B4GALT5 significantly promoted the proliferation of OC cells. Upon analyzing gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), it was discovered that B4GALT5 played a crucial role in the extracellular matrix, particularly in collagen-containing structures, and exhibited correlations with ECM-receptor interactions, transcriptional dysregulation in cancer, as well as the interleukin-1 receptor signaling pathway. Furthermore, there is a clear link between B4GALT5 and the tumor immune microenvironment in OC. Moreover, B4GALT5 exhibits favorable expression levels across various types of cancers, including CHOL, KIRC, STAD and UCES. Conclusion In conclusion, it is widely believed that B4GALT5 plays a pivotal role in the growth and progression of OC, with its heightened expression serving as an indicator of unfavorable outcomes. Moreover, B4GALT5 actively participates in shaping the cancer immune microenvironment within OC. This investigation has the potential to contribute significantly to a deeper understanding of the substantial involvement of B4GALT5 in human malignancies, particularly OCs.